On the investigation of electroanaesthesia in Labeo rohita under DC and PDC electric field - Chakraborty, Nabanita; De, Aakash; Ghosh, Sandip Kumar; De, Tarun Kumar (Journal of Fisheries, 2022)
This study investigates electroanaesthesia under Direct Current (DC) and three low frequency Pulsed Direct current (PDC) of 1 Hz, 3 Hz and 6 Hz in Labeo rohita. All the current types in this study were effective in anaesthetizing L. rohita with fast induction and rapid recovery period in all fishes. The threshold value of voltage gradient (V cm–1) for inducing anaesthesia was higher in DC than PDCs. Opercular movements were significantly lower during anaesthesia, significantly higher one minute after recovery in all current types and reduced significantly in DC, PDC 1 Hz and PDC 3 Hz after 10 min of recovery from anaesthesia. Blood glucose level returned to the near control values after 8 hours of exposure in all current types in this study. DC sharp rise and PDC 3Hz may be preferred for inducing anaesthesia considering the recommended criteria of anaesthetic induction and recovery time. Result of this study indicates that electroanaesthesia technique with fast induction and rapid recovery may proffer a cost effective, safe and ecofriendly alternative for aquaculture activities in L. rohita.